2014
DOI: 10.1111/jth.12412
|View full text |Cite
|
Sign up to set email alerts
|

Human liver sinusoidal endothelial cells but not hepatocytes contain factor VIII

Abstract: Summary. Background: Although the liver is the major site of coagulation factor VIII (FVIII) synthesis, the type of cells producing FVIII within the liver is still unclear. Objectives: To measure FVIII in extracts of primary liver sinusoidal endothelial cells (LSECs) and hepatocytes, thereby preventing potential bias resulting from the modifications of the cell phenotype that can take place during in vitro culture. Methods: LSECs were purified by flow cytometry cell sorting on the basis of their coexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
142
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 26 publications
3
142
0
2
Order By: Relevance
“…19,20 However, this strategy may be limited by the intrinsic inability of the human hepatocyte to fully synthesize and secrete factor VIII, despite the presence of mRNA. 6 This may explain, at least in part, the higher dose of vectors required for expression of factor VIII compared to factor IX. On the other hand, despite the limiting effect on the efficacy of factor VIII secretion, the use of hepatocyte-specific expression is a favorable strategy in terms of immune tolerance induction to factor VIII, which is the most serious and common complication (~20%) of hemophilia A treatment.…”
Section: What Are the Implications Of These Findings For Cellular Andmentioning
confidence: 99%
See 3 more Smart Citations
“…19,20 However, this strategy may be limited by the intrinsic inability of the human hepatocyte to fully synthesize and secrete factor VIII, despite the presence of mRNA. 6 This may explain, at least in part, the higher dose of vectors required for expression of factor VIII compared to factor IX. On the other hand, despite the limiting effect on the efficacy of factor VIII secretion, the use of hepatocyte-specific expression is a favorable strategy in terms of immune tolerance induction to factor VIII, which is the most serious and common complication (~20%) of hemophilia A treatment.…”
Section: What Are the Implications Of These Findings For Cellular Andmentioning
confidence: 99%
“…These include acute myeloid leukemia and acute lymphoblastic leukemias caused by translocations of the Mixed Lineage Leukemia (MLL) gene, [2][3][4] fusions of the HOXA9 gene that produce a novel HOXA9-NUP98 fusion protein in acute myeloid leukemia, 5 and T-cell acute lymphoblastic leukemias that have translocations between the TCRβ and HOXA9/A10 loci. 6 Interestingly however, despite this seemingly central role in a subset of acute leukemias, Hoxa9 expression alone is only weakly oncogenic in mouse leukemia models and usually requires a second "hit" via overexpression of Meis1, 7,8 or in some cases Pbx3. 9 Much work has been done trying to understand the molecular function of the HOXA9 protein.…”
Section: What Are the Implications Of These Findings For Cellular Andmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed that endothelial cells, but not hepatocytes, contained measurable levels of FVIII coagulant activity. 8 Before these studies, there existed conflicting reports and significant speculation that endothelial cells, hepatocytes, and hematopoietic and mesenchymal cells were important contributors to the circulating pool of FVIII. Without clinical evidence of nonendothelial FVIII biosynthesis and nonhepatocyte FIX biosynthesis and with no existing source/transplantation protocols for endothelial or hepatocyte stem cells, allogeneic transplantation does not appear to be a viable near-term option.…”
Section: Origins and Limitations Of Fviii And Fix Biosynthesismentioning
confidence: 99%